Alterations In The Profile Of Blood Cells Of Wistar Rats Induced By Long-Term Ingestion Of Chlorpyrifos - SAROJNI TRIPATHI; AJAI KUMAR SRIVASTAV (International Journal of Pharma and Bio Sciences, 2010)
Male Wistar rats were divided into three groups -- A, B and C. Two groups (B and C) of animals were daily administered orally chlorpyrifos at a dose of 5 and 10 mg/kg b wt., respectively. One group (A) was employed as control. Rats were sacrificed 24 h after last dose on 1st, 2nd, 4th, 6th, and 8th week after initiation of the experiment. Morphological alterations in blood cell profiles induced by chlorpyrifos treatment were investigated on hematological preparations made by routine methods. Results of the present study indicate that chlorpyrifos provoked an alteration of rat erythrocyte morphology from the normal discoid shape to other forms such as echinocytes, dacrocytes, schistocytes etc. Following chlorpyrifos treatment, few faded red blood cells were encountered. Many cells were degenerated thus at places cell debris were present. Few nucleated red cells were also seen.